Women Reprimanding Women: The Gothic Parody and its Social Criticism - Kerstin-Anja Münderlein (European Journal of American Studies)
In the late eighteenth century, the Gothic parody, ridiculing the generic traits of the Gothic novel, often directed their humor at the parody heroine. Specifically, the didactic Gothic parody aimed at educating the heroine into a normative, gender-role conforming young woman who rejects the excesses of the Gothic in favor of an adherence to normative conduct. The use of humor in the Gothic parody serves to “normativize” the heroine of the Gothic parody, which will be exemplified by Mary Charlton’s Rosella (1799) and Jane Austen’s Northanger Abbey (1817). Despite the similarities in their plots, the novels differ in their application of parody directed at the protagonist. Austen’s must reject her overindulged imagination and learn to differentiate reality and fiction; Charlton’s needs to endure the overindulged imagination of her guardians, whose penchant for confusing reality and fiction nearly leads to Rosella’s downfall. While both novels thus discuss the dangers of confusing reality and fiction, their targets for ridicule, the degree to which the respective characters are affected by their delusions, and the degree of “real” danger these delusions can cause differ significantly.